Stock composition of cryptic Atlantic sturgeon (Acipenser oxyrinchus oxyrinchus) in the Restigouche River and estuary, Canada - N. J. Daigle; S. White; B. A. Lubinski; R. Johnson; D. C. Kazyak; C. E. Verhille; C. A. Gillis; C. F. D. Sacobie (Scientific Reports)
Abstract The Atlantic sturgeon (Acipenser oxyrinchus oxyrinchus) is an important species in eastern North America due to its conservation status and cultural significance. Local Mi'gmaw fishers have reported an increase in sturgeon sightings over the last decade in the Restigouche River and estuary. Mi’gmaw Knowledge, oral history, and archaeological finds attest to their historical presence in the region; however, the river is not a documented habitat for Atlantic sturgeon in Western literature. Based on community interest and concern, the Gespe’gewa’gi Institute of Natural Understanding co-developed a Two-Eyed Seeing collaboration to learn more about these sturgeon. Here, we investigate their genetic origin via microsatellite analyses and hypothesized that they would originate from the closest spawning habitat, the St. Lawrence River. We found that, overall, the largest contributor to our Atlantic sturgeon sampled from the Restigouche River system was the St. Lawrence River (85.7% of samples), followed by the Wolastoq (3.6%), then a mixture of the St. Lawrence, the Wolastoq, the Kennebec, and/or the Hudson River populations (10.7%). Improving our understanding of the distribution of Atlantic sturgeon through microsatellite analyses and leveraging range-wide genetic baselines directly assesses the genetic origin of unknown stock compositions and can support the future co-management of the species.